2006
DOI: 10.3892/or.16.4.647
|View full text |Cite
|
Sign up to set email alerts
|

Cystatins in non-small cell lung cancer: Tissue levels, localization and relation to prognosis

Abstract: Cystatins regulate tumour-associated cysteine proteases, however, their role in tumour progression is not clear yet. To assess their relevance in the progression of nonsmall cell lung cancer (NSCLC) the protein level, cysteine protease activity (CPI) and localization of type I (stefins A and B) and type II (C, E/M and F) cystatins were defined in tumours and control lung counterparts from 165 patients. The medians of CPI activity, stefins A and B were significantly greater in tumour than in lung tissue (2.1-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 35 publications
1
37
0
Order By: Relevance
“…Correspondingly, data concerning the role of cystatin C in HNC patients is likewise conflicting. While one report showed increased levels of serum cystatin C in HNC patients when compared to healthy controls [35], suggesting a pathological role of cystatin C in HNC, another investigation demonstrated that high levels of cystatin C in tumor tissue had a protective effect, being associated with prolonged survival [32]. Similar results were published for breast [15,16] and lung cancer [11].…”
Section: Discussionmentioning
confidence: 62%
“…Correspondingly, data concerning the role of cystatin C in HNC patients is likewise conflicting. While one report showed increased levels of serum cystatin C in HNC patients when compared to healthy controls [35], suggesting a pathological role of cystatin C in HNC, another investigation demonstrated that high levels of cystatin C in tumor tissue had a protective effect, being associated with prolonged survival [32]. Similar results were published for breast [15,16] and lung cancer [11].…”
Section: Discussionmentioning
confidence: 62%
“…Moreover, cystatin C is thought to play a role in protein homeostasis in the extracellular compartment, inhibiting inappropriate hydrolytic degradation by proteinases released from dying cells [16]. Cystatin C may also be released from infiltrated inflammatory cells such as macrophages and neutrophils [17]. Higher serum concentrations of Cyst C were also determined in patients with ovarian cancer [18], colorectal cancer and melanoma [19] in comparison with healthy people.…”
Section: Discussionmentioning
confidence: 99%
“…According to Werle and Kos [14,17] higher total concentrations of Cyst C found in sera of patients with lung, colorectal and melanoma cancer suggested the enhanced secretion of cystatin C from tumor cells, increasing at the same time the intracellular proteolytic potential of cysteine proteases. Moreover, increased levels of cystatin C in tumor tissues have been shown to correlate with favorable prognosis of cancer patients [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…The 96 amino acid-long deduced protein (termed CYTA_SUBDO) has a size of 10·828·Da and a pI of 6.4. The sponge cystatin shares highest sequence similarity with the human sequences cystatin A and cystatin B, with an 'expect value' (Coligan et al, 2000) of 3e -04 [cystatin B (Joensuu et al, 2007); cystatin A (Werle et al, 2006)]. The sponge cystatin (A) Protein extracts were prepared from the outer lamellar region of the spicules (la; lane a) or from total spicule (to; lane b) and size separated by 10% SDS-PAGE.…”
Section: W E G Müller and Othersmentioning
confidence: 99%